Pengaruh Perilaku Konsumen Sadar Lingkungan Dan Niat Pembelian Produk Ramah Lingkungan Terhadap Perilaku Pembelian Produk Ramah Lingkungan (Studi Kasus Pada Konsumen Zero Waste Indonesia) - Farhan Maulana; Bambang Hermanto; Rivani Rivani (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
The goal of this research is to demonstrate the correlation between ecologically conscious consumer behavior, green purchase intention, and green purchase behavior within a Zero Waste Indonesia community. Data was gathered from 175 consumers in Zero Waste Indonesia. A method of research that deals with the collection of numerical data and statistical analysis was used in this study, using questionnaires as the primary data collection technique and journal and national news sources for secondary data collection. The results of this research indicate that green purchase intention is influenced by ecologically conscious consumer behavior, green purchase behavior is influenced by green purchase intention, and ecologically conscious consumer behavior is not affected by green purchase behavior.